Pengaruh Economic Value Added, Ukuran Perusahaan dan Total Aset Turnover terhadap Return Saham di Sektor Properti dan Real Estate Pada BEI tahun 2020-2023 - Putri Khairani; Warsani Purnama Sari; Alfriado Leonard Noprian Dolok Saribu (Mahesa Research Center, 2024)
The purpose of this study is to determine the effect of economic value added, company size, and total asset turnover on stock returns. Based on the research hypothesis that has been determined, it is known that economic value added, company size, and total asset turnover have a positive and significant effect on stock returns. The type of quantitative research with a causal associative approach. The population is 27 mining sector companies with a purposive sampling technique of 15 companies over 4 years with a total of 60 data. The data processing technique uses multiple linear regression analysis. The results of the study indicate that economic value added does not affect stock returns, while company size and total asset turnover have a significant positive effect on stock returns and simultaneously economic value added, company size and total asset turnover have a positive and significant effect on stock returns.